2022
DOI: 10.1200/jco.21.02228
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease After Autologous Stem-Cell Transplant for Patients With Myeloma: Prognostic Significance and the Impact of Lenalidomide Maintenance and Molecular Risk

Abstract: PURPOSE Minimal residual disease (MRD) can predict outcomes in patients with multiple myeloma, but limited data are available on the prognostic impact of MRD when assessed at serial time points in the context of maintenance therapy after autologous stem-cell transplant (ASCT) and the interaction between MRD and molecular risk. METHODS Data from a large phase III trial (Myeloma XI) were examined to determine the relationship between MRD status, progression-free survival (PFS), and overall survival (OS) in post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…In their study, in accord with prior meta-analyses focusing on MRD status and clinical outcomes in patients with newly diagnosed multiple myeloma, [6][7][8] de Tute et al 10 found MRD negativity to be associated with improved PFS (HR 5 0.21; P , .0001) and OS (HR 5 0.33; P 5 .0077). Their findings were very similar when restricted to those patients in complete response or near complete response.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In their study, in accord with prior meta-analyses focusing on MRD status and clinical outcomes in patients with newly diagnosed multiple myeloma, [6][7][8] de Tute et al 10 found MRD negativity to be associated with improved PFS (HR 5 0.21; P , .0001) and OS (HR 5 0.33; P 5 .0077). Their findings were very similar when restricted to those patients in complete response or near complete response.…”
mentioning
confidence: 55%
“…9 To our knowledge, the Myeloma XI trial is one of the largest studies conducted to date (N 5 2,568) focusing on transplant-eligible patients with newly diagnosed multiple myeloma. 10 In the current paper, the authors examined data from Myeloma XI to determine the relationship between MRD status, PFS, and OS in post-HDM-ASCT patients randomly assigned to lenalidomide maintenance or no maintenance at 3 months after HDM-ASCT (N 5 1,248; Fig 1). 10 MRD status was assessed by flow cytometry (median sensitivity 0.004%) before maintenance random assignment (HDM-ASCT 1 3) and 6 months later (HDM-ASCT 1 9).…”
mentioning
confidence: 99%
“…1,2 Persistent MRD in the setting of continuous therapy for transplant-ineligible 3,4 and relapsed patients, 5 as well as after induction and intensification in transplant-eligible patients, [6][7][8] is significantly associated with inferior survival. There are promising, yet scarce, data on the clinical value of MRD assessment during continuous [8][9][10] or fixed-duration 6 maintenance therapy. In contrast, there is virtually no information on patients' MRD status during observation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is virtually no information on patients' MRD status during observation. 10 Paradoxically, maintenance and observation are the disease settings where MRD status is anticipated to help tailor treatment duration. 11,12 Historically, MRD has been evaluated at specific single time points during therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation